Apoptosis resistance in tumor cells - Mashima, Tetsuo (Kluwer Academic Publishers, 1998)
Various antitumor agents induce apoptotic cell death in tumor cells. Since the apoptosis program in tumor cells plays a critical role in the chemotherapy-induced tumor cell killing, it is suggested that the defect in the signaling pathway of apoptosis could cause a new form of multidrug resistance in tumor cells. This article describes the recent findings concerning the mechanisms of chemotherapy-induced apoptosis and discusses the implication of apoptosis resistance in cancer chemotherapy.